THE EFFECTIVENESS OF WORDWALL-BASED STEM LEARNING ON UNDERSTANDING MATHEMATICS SUBJECT MATTER: OPERATIONS WITH WHOLE NUMBERS FOR ELEMENTARY SCHOOL STUDENTS - Gantheng Listyoadi; Mar’atu Zahra; Unik Ambar Wati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
In today’s educational landscape, many students struggle to develop a deep understanding of mathematical concepts, particularly in number operations, due to conventional and abstract teaching methods that lack real-world relevance. This study examines the effect of integrating STEM education (Science, Technology, Engineering, and Mathematics) with the Wordwall platform on enhancing elementary students' understanding of integer operations. Using a quantitative one-group pretest–posttest design, the research involved 46 fourth-grade students from SD Muhammadiyah Condongcatur. Students completed pre- and post-tests following the STEM–Wordwall learning intervention. The results revealed a statistically significant improvement in students’ mathematical understanding, with a moderate effect size (Cohen’s d=-0.540). The 95% confidence interval supported the effectiveness of the intervention. These findings align with previous studies emphasizing the positive influence of interactive digital tools on mathematical cognition and student engagement. Thus, integrating STEM principles with Wordwall effectively enhances learning outcomes and should be adopted to promote engaging mathematics instruction in primary education.